Pelatihan Canva untuk Meningkatkan Keterampilan Desain Media Guru SD Negeri 7 Salabose - Syah, Laode Muh Zulfardin; Zam'ah, Zam’ah; Manullang, Ketrin Rinayanti; Munthakhabah, Cita St.; Wahid, Anwar; Nurhuda, Nurhuda; Ismail, Ismail; Aksanuddin, Aksanuddin; Indriani, Tesya; Ramadani, Mutiara (Jurnal Nusantara Mengabdi, 2026)
Purpose: This study aims to improve the digital competence of teachers at SD Negeri 7 Salabose in designing visual learning media using the Canva platform. The program addresses teachers’ limited digital literacy and ability to create technology-based instructional materials. Methodology: The activity was carried out through a one-day intensive workshop involving 33 teachers. It included material presentation, demonstrations of Canva for Education features, hands-on design practice, and evaluation through online questionnaires measuring usefulness, ease of use, and satisfaction. Results: Teachers showed improved understanding of Canva’s features and successfully created posters and interactive slides. Evaluation results indicated high satisfaction, with a Reaction score of 94.2% and a Behavior score of 92.7%, demonstrating strong motivation to apply Canva in classroom learning. Conclusions: The workshop effectively enhanced teachers’ digital competence and readiness to integrate visual media into teaching. Short, structured digital training proved beneficial in fostering innovative and technology-integrated learning practices in elementary education. Limitations: The workshop duration was limited to one day, which allowed only basic-level mastery of Canva features. Contributions: This study contributes to strengthening teachers’ digital competence, promoting innovative instructional practices, and supporting the integration of visual learning media in elementary education.